Protective Effects of Cilastatin against Vancomycin-Induced Nephrotoxicity. (4th October 2015) - Humanes, Blanca; Jado, Juan Carlos; Camaño, Sonia; López-Parra, Virginia; Torres, Ana María; Álvarez-Sala, Luís Antonio; Cercenado, Emilia; Tejedor, Alberto; Lázaro, Alberto
Abstract : Vancomycin is a very effective antibiotic for treatment of severe infections. However, its use in clinical practice is limited by nephrotoxicity. Cilastatin is a dehydropeptidase I inhibitor that acts on the brush border membrane of the proximal tubule to prevent accumulation of imipenem and toxicity. The aim of this study was to investigate the potential protective effect of cilastatin on vancomycin-induced apoptosis and toxicity in cultured renal proximal tubular epithelial cells (RPTECs). Porcine RPTECs were cultured in the presence of vancomycin with and without cilastatin. Vancomycin induced dose-dependent apoptosis in cultured RPTECs, with DNA fragmentation, cell detachment, and a significant decrease in mitochondrial activity. Cilastatin prevented apoptotic events and diminished the antiproliferative effect and severe morphological changes induced by vancomycin. Cilastatin also improved the long-term recovery and survival of RPTECs exposed to vancomycin and partially attenuated vancomycin uptake by RPTECs. On the other hand, cilastatin had no effects on vancomycin-induced necrosis or the bactericidal effect of the antibiotic. This study indicates that cilastatin protects against vancomycin-induced proximal tubule apoptosis and increases cell viability, without compromising the antimicrobial effect of vancomycin. The beneficial effect could be attributed, at least in part, to decreased accumulation of vancomycin in RPTECs.